Feedback and written mathematics communication: a pen pal exchange - Barbosa, Ana (2022)
This paper describes a study that aims to understand and characterize the written communication of future primary education teachers in a context of a pen pal exchange with 3rd grade students (8 years old), in particular the nature of the feedback. We followed a qualitative methodology, where data were collected through observation, written productions (letters) and an interview with the participants. Each future teacher was paired with two students, and four letters were written by the participants over the course of ten weeks. The first letter had the intent of presenting themselves and knowing the recipient. In the following letters the dialogue was continued and the pre-service teachers posed challenging mathematical tasks for the students to solve and for them to give feedback. We focused our analysis in the quality of written communication/feedback, the perceptions of future teachers about the potential of this experience and difficulties experienced. The dynamics of the correspondence exchange allowed the records to be prepared with great commitment. When selecting the tasks, they realized the importance of knowing the curricular guidelines, as well as the contents that the students were addressing. The tasks posed varied from exercises/problems centred on contents addressed by the students. The feedback sent was quite diverse. In some cases, it was not informative, and was even quite superficial; in other situations, the comments provided indicated hints for future action, seeking to promote learning. The exchange of correspondence by letter enabled the sharing of ideas, access to mathematical knowledge, the formulation of tasks, promoting the development of written communication.